Effects of maternal Bromocriptine and Melatonin treatments on fetal development : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Animal Science at Massey University, Palmerston North, New Zealand - Wigati, Sri (Massey University, 1996)
A previous study (Jenkinson et al., 1994) has proposed that lowered birth weights of autumn (May)-born lambs compared with those of spring (August)-born lambs are due to a direct seasonal effect on placental size, which in turn mediates a slower fetal growth. The effect of season on placental and fetal development is established early in pregnancy (by day 84 of gestation), and is suggested to be mediated by seasonal differences in circulating prolactin concentrations in the dams and/or fetuses (Jenkinson et al., 1994; McCoard et al., 1996). Plasma prolactin concentrations are likely to be very high in autumn-lambing ewes (December-mated ewes) during the early- to mid-gestation period December-February due to a seasonal (primarily daylength) effect (Pearson et al., 1993; Pearson et al., 1996). The study described herein was carried out in an attempt to increase birth weights of autumn-born lambs by improving placental development and hence fetal growth via manipulation of maternal prolactin concentrations. Treatments with bromocriptine (a dopaminergic agonist) and melatonin early in gestation were tested for their ability to reduce maternal and/or their fetal circulating prolactin concentrations, improve placental development and hence increase fetal growth and birth weights.
Keywords: Sheep; Fetuses; Lambs; Growth; Birth weight; Effects of drugs on